Global Trends in LADA Type Diabetes Research: A Bibliometric Analysis of Publications from Web of Science and Scopus, 1994–2024 - Khatimya Kudabayeva; Bibigul Tleumagambetova; Yerlan Bazargaliyev; Raikul Kosmuratova; Aliya Zhylkybekova (Journal of Diabetes Research)
The prevalence of T2DM has been increasing dramatically over recent decades, about 537 million people in 2021. LADA type diabetes, a subtype of diabetes that exhibits characteristics of both T2DM and autoimmune beta-cell destruction similar to T1DM, but with a later onset. The aim of this study is to analyze the main research field on LADA type, including analysis of countries, institutions, journals, authors, and keywords. This research utilized a descriptive bibliometric design. We collected and analyzed data from 672 publications indexed in the Web of Science and Scopus databases, covering the period from 1994 to January 2024. The bibliometric analysis included English-language research articles that involved studies on patients with LADA type diabetes, aged 18 years or older. RStudio and the Bibliometrix R package were used for data merging and for performing statistical and visual analyses. The annual publication shows an upward trend over the period, with the highest number of publications per year in 2021. The study showed that China leads in the number of articles, with 101 papers published. The United Kingdom demonstrates significant international collaborations, particularly with Germany. The top institutions in terms of the number of published articles are the Norwegian University of Science and Technology in the Kingdom of Norway, followed by the Central South University in China. Tuomi has shown significant long-term publication impact, while Zhou ranks among the most frequently cited authors. Diabetes Care is one of the most important scientific journals in diabetology with the highest impact factor of 16.2. This abstract summarizes a comprehensive bibliometric analysis that provides insights into the global research field of LADA type, underscoring the importance of international collaboration and the significant contributions of leading countries and institutions in shaping our understanding of this complex subtype of diabetes.